Let the nations be glad : the supremacy of God in missions - Piper, John, 1946- (Baker Books, 1993)
In this sequel to The Supremacy of God in Preaching, John Piper draws on key biblical texts to show that worship is the ultimate goal of the church, and that proper worship fuels missions. The author addresses the role of prayer, universalism and annihilationism, the incentives of sovereign grace for world evangelization, and the task of reaching unreached peoples. Let the Nations Be Glad! will help students of missions reflect on the relationship between church and mission and on the role of every Christian in going out to all the world. - Back cover.